Pengaruh Senam Hamil Terhadap Ketidaknyamanan Fisik Ibu Hamil Trimester Ke III Di Puskesmas Pembina Palembang - yuniza yuniza; Murbiah Murbiah; Jumiati Jumiati (Masker Medika, 2023)
Abstract Background : Pregnancy is a transition between life before and after the birth of a child. These changes are considered as a period of undergoing a preparation process both physically and psychologically, complaints caused by an enlarged abdomen, anatomical changes and hormonal changes will cause complaints in pregnant women such as low back pain, swelling and cramps in the legs, this discomfort causes sleep disturbances and affect the fetus in the womb. Efforts to overcome this include pregnancy exercise. Pregnancy exercise is a method that helps provide relaxation for the third trimester, pregnancy exercise is carried out at least 3 meetings in 2 weeks. Research objective: To determine the effect of pregnancy exercise on the physical discomfort of third trimester pregnant women. Research Method: this research was conducted with a one group pretest – posttest design. The sample of this research is 28 respondents. Results: From the statistical test results used that the pretest average (73.69) and posttest average (60.79). Conclusion: there is an effect of pregnancy exercise on the physical discomfort of third trimester pregnant women. Keywords: Implementation of pregnancy exercise, Physical discomfort for third trimester pregnant women